Cleaning potential of surfaction of fouled ultrafiltration (UF) membranes - Mohd Hafez Mohd Isa,; Richard A. Frazier,; Paula Jauregi, (Universiti Kebangsaan Malaysia, 2012)
Biosurfactants are microbially produced surface active agents that offer better biodegradability and lower toxicity than chemically synthesized surfactants because of their biogenetic origin. One of the most surface-active biosurfactants known is surfactin, a cyclic lipopeptide produced by various strains of Bacillus subtilis. In this study, the cleaning potential of surfactin on ultrafiltration (UF) membranes fouled with BSA was studied using centrifugal UF devices of 50 kDa and 100 kDa MWCO polyethersulfone (PES) membranes. Mechanisms of bovine serum albumin (BSA) displacement by surfactin on fouled UF membranes were studied using dynamic light scattering (DLS) technique and surface tension measurements. Hydrodynamic diameter and surface tension measurements of BSA-surfactin mixtures showed that the surfactin was efficient in displacing BSA fouled on UF membranes due to strong electrostatic repulsive interactions involved at pH8.5. This study demonstrated that surfactin can be used to effectively clean fouled UF membranes